Performance through diversity and inclusion leveraging organizational practices for equity and results - Bernstein, Ruth Sessler, 1957-; Salipante, Paul F., 1945- (Routledge, 2021)
"This book provides practical guidance for managers, leaders, diversity officers, educators, and students to achieve the benefits of diversity by focusing on creating meaningful, inclusive interactions. Implementing inclusive interaction practices, along with accountability practices, enhances performance outcomes for the organization and improves equity for members of historically underrepresented and marginalized groups. The book highlights the need to challenge existing approaches that have overemphasized representational-that is, numerical-diversity. For many decades the focus has been on this important first step of increasing the numbers of underrepresented groups. However, moving beyond representation towards a truly inclusive organizational culture that produces real performance and equity has been elusive. This book moves the focus from achieving numerical diversity to achieving frequent, high quality, equitable, and productive interactions that enable individuals to leverage their distinctive talents, and provides the steps to do so. The benefits of this approach occur at the individual, workgroup and organizational levels. Real-life examples of good inclusive practices are provided from across the for-profit, nonprofit and governmental sectors and in various organizational contexts. The book is ideal not only for those charged with diversity, equity and inclusion efforts in organizations, but also for organizational leaders and managers who can create and/or support the implementing of inclusive organizational practices and also for postgraduate and undergraduate students studying human resource management, organizational behavior, management, or diversity, equity and inclusion"--